Paradoxes of the democratization of higher education - Youn, Ted I. K. (Bingley, U.K. : Emerald, 2016)
Research in Social Problems and Public Policy (RSPPP) is a peer-reviewed series devoted to the sharpening and reshaping of scientific discourse involving the intersection of social problems and public policy. In particular, it is interested in the analysis of the potential failure of public institutions to fulfil their obligations to the broader society. Multidisciplinary in nature, Research in Social Problems and Public Policy presents important themes of: social/crime problems and their treatment; criminal justice; law and public policy; crime, deviance and social control; courts and diversion programs; therapeutic jurisprudence, restorative justice and alternative dispute resolution; law and society; substance use/abuse and treatment; health and society; and institutional interaction. The articles have a clear connection to the series' main focus, lying at the confluence of social problems and public policy. This volume focuses on the democratization of higher education.
The intersection of student loans and social class: exploring borrowers' journeys into debt and repayment / Elissa Chin Lu -- Cooling out and leveled aspirations among low-income university STEM students / Heather Haeger, Regina Deil-Amen -- Predictors of low-SES student persistence from the first to second year of college / Heather T. Rowan-Kenyan, Rebecca D. Blanchard, Brian D. Reed, Amy K. Swan -- Country roads take me?: an ethnographic case study of college pathways among rural, first-generation students / Sarah Elizabeth Beasley -- The paradoxes of pathways from college aspirations to attendance / Karen D. Arnold, Katherine Lynk Wartman -- Mapping institutional legitimacy in meeting of expanding demand for education / Elizabeth Storrs.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Educational strategies & policy; Democracy and education; Higher education and state; Education, Higher -- Aims and objectives